Inédito viável na rede de atenção psicossocial: construções coletivas diante da apreciação de seus trabalhadores - Souto, Valquíria Toledo (2022)
This research has as a general objective: to analyze how the collective work of workers has driven the construction of unpublished viable, in the perspective of the transformation and consequent qualification of care in the Psychosocial Care Netw ork. . It is based on Paulo Freire's theoretical referential, articulating his critical theory to Appreciative Research, through the development of the 4D Cycle (Discovery, Dream, Design and Destiny) Sixteen workers from the Psychosocial Care Network of Santa Maria, Rio Grande do Sul, Brazil, participated in the research in the period from December 2019 to July 2020. Data production occurred through semi structured interviews and focus groups, in person and remotely. Data analysis was performed through codin g, categorization, and identification of themes, following steps described by Green, Sampieri, Colado, and Lucio. The ethical aspects of the research were respected, being approved by the Research Ethics Committee and registered in the P lataforma Brasil. A s results, I identified five major themes: what gives life, what worked out, utopias of workers in the Psychosocial Care Network, collectivizin is us in communion. g dreams, and the network The results showed that what worked (best practices) was the relat ionship built with users, collective and multiprofessional work, partnerships with the intersectoral network, the relationship with the Multiprofessional Residency, participation in discussion and management spaces, the work based on the territory, group a ctivities developed with service users, matrix support, social control initiatives, such as the creation of a Mental Health Management Council, and the experience of creating a Harm Reduction School. What gives life to work is its conformation in a collec tive, especially when there is dialogue, support, commitment, sharing among its workers. It is also its interdisciplinary character, its dynamism, politics and affectivity. Working in the Network enables teachingservice integration, makes it possible to b e an agent of change (in the user's life). The dreams for the Network were within what is already recommended: a structured network (with sufficient human and structural resources); a better defined care flow (collectively); closer approach to management; a work dynamic that is closer to the reality/territory of users, which manages to act on the determinants with health prevention actions; that workers are committed, that there is investment in care actions for the mental health of the worker, who is vulne rable, requires recognition, support and appreciation. The workers have planned actions so that some of these dreams can become viable unpublished. They want to increase the collective involved and committed to changes in the Network and approaching manage ment. They will do this by improving the dissemination of meeting spaces that already exist, such as the Mental Health Forum, Network Meetings, Interequipes, and sensitizing management so that they can also participate. The partnership with the Municipalit y's Permanent Education Center is understood as fundamental, which will be mobilized to expand actions, support the organization of matrix support actions, as well as expand and qualify the dialogue with educational institutions, improving their feedback t o the services. This research contributes to the record of the processes experienced throughout the history of the Network studied, giving visibility to its best practices, its strengths, challenges and, especially, its subjects (workers perceived as agent s of change).I recognize that the qualification of work in the Psychosocial Care Network, and therefore, of assistance to the user, which gives meaning to the actions of these workers, is a challenge. It involves multiple subjects in a process that needs t o be one of communion and solidarity between beings. It is not possible to advance without public policies that guarantee dignified and quality care. Also, it is not possible to conquer them without an organized collective, aware of its historical, ethical , political, moral and affective commitment, which fights for change.